REGULATORY AMBIGUITY AND ITS IMPLICATIONS FOR THE NEUTRALITY OF THE STATE CIVIL APPARATUS IN THE VORTEX OF PRACTICAL POLITICS - Suswanta, Suswanta; Setiawan, Anang (CosmoGov: Jurnal Ilmu Pemerintahan, 2023)
Violations of the neutrality of the State Civil Apparatus (ASN) in public spaces in the simultaneous Regional Head Elections (Pilkada) in 2020 became an actual and factual phenomenon. In the Election Insecurity Index (IKP) for the simultaneous regional elections in 2020, violations of ASN neutrality are at the top of the rankings, which occur in 167 districts/cities out of 270 regions that implement them. Regulations to maintain the neutrality of the ASN in the political maelstrom are practically readily available, but explicitly, there are legal loopholes that allow for violations to occur. The study results show that the breach of ASN neutrality in the simultaneous regional elections in 2020 is substantially rooted in the ambiguity of regulations that place regional heads who are, in fact, political officials as executors of coaching and cracking down on violations of ASN neutrality. The implication of the ambiguities of the regulation is the establishment of a negative stigma against the professionalism of ASN as a public official, regional heads as Civil Service Supervisory Officers in the regions do not follow up on recommendations for sanctions from KASN, and the massive violations. Based on the result, regulatory reforms are urged to ensure that the development and enforcement of breaches of ASN neutrality are not controlled by political officials but by career officials.gb777